Differences in Knowledge, Attitudes, Actions, and Sources of Information on Adolescent Reproductive Health - Delvia Basri, Mira; Maulana, T; Sofia, Sofia; Marthoenis, M.; Mawarpury, Marty (Journal of World Science, 2023)
Adolescence is a critical period during which a person lays the foundation for his reproductive life. Teenagers in pesantren and schools have different environments, so that will affect their knowledge. This study aims to determine and analyze differences in knowledge, attitudes, behaviours, and sources of adolescent reproductive health information between high school girls and young women who stay in Islamic boarding schools in Banda Aceh City. This type of research is comparative with a cross-sectional design. The population is all young women from class X and XI Islamic boarding schools and 330 young women from Banda Aceh City High School and Babun Najah Islamic Boarding School. The sample is the total population. The results of the study obtained differences in knowledge, attitudes, behaviours, and sources of adolescent reproductive health information between high school girls and young women in pesantren. The level of knowledge, attitudes, and sources of information affect reproductive health behaviour/actions. Information source variables are the most influential variables on reproductive health behaviours/actions. This study concludes that knowledge and sources of information are higher in high school children than in pesantren. In contrast, actions/behaviours in high school children are lower than in pesantren.